3 The Revised Statutes, Code, and General Laws of the State of New York 3330, § 2 (Clarence F. Birdseye ed., 1890) - (:unkn) unknown (My University, 1890)
Prohibited carrying with intent to use any slungshot, billy, sand-club, metal knuckles, dagger, dirk, dangerous knife. Violators guilty of a felony. Minors guilty of a misdemeanor.
Keywords: CARRY - NON-GUN ARMS